2023
DOI: 10.2196/47777
|View full text |Cite
|
Sign up to set email alerts
|

Teaching LGBTQ+ Health, a Web-Based Faculty Development Course: Program Evaluation Study Using the RE-AIM Framework

Abstract: Background Many health professions faculty members lack training on fundamental lesbian, gay, bisexual, transgender, and queer (LGBTQ+) health topics. Faculty development is needed to address knowledge gaps, improve teaching, and prepare students to competently care for the growing LGBTQ+ population. Objective We conducted a program evaluation of the massive open online course Teaching LGBTQ+ Health: A Faculty Development Course for Health Professions E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…For example, integrating information about disparities in access to DBS into continued medical education modules for physicians, particularly in primary care and neurology, could be an impactful approach to raise awareness and communicate directly with the individuals capable of making actionable change. There is some evidence to suggest that integration of DEI training into continued medical education modules may improve provider skills in providing culturally competent services and patient satisfaction [ 65 , 66 ]. Previous studies have also found that incorporating DEI material into graduate medical education was feasible and well received [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, integrating information about disparities in access to DBS into continued medical education modules for physicians, particularly in primary care and neurology, could be an impactful approach to raise awareness and communicate directly with the individuals capable of making actionable change. There is some evidence to suggest that integration of DEI training into continued medical education modules may improve provider skills in providing culturally competent services and patient satisfaction [ 65 , 66 ]. Previous studies have also found that incorporating DEI material into graduate medical education was feasible and well received [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE‐AIM) framework is a common and practical tool that can evaluate the implementation longitudinally from the initial reach of the program through sustained maintenance over time (Table 2). 15,16 RE‐AIM is versatile and has been previously used to evaluate several online medical education curricula during COVID‐19 17‐20 as well as mentoring programs for faculty underrepresented in medicine 21 . RE‐AIM has advantages over narrower tools, such as the Kirkpatrick model, 22 by providing a more expansive view of the effect of the innovation and its implementation.…”
Section: Application To Medical Educationmentioning
confidence: 99%